2016
DOI: 10.1016/j.jlumin.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

9-Arylvinyl- and 9,10-bis(arylvinyl)-anthracenes with phenyl and naphthyl as aryl moieties: Differential aggregation behaviors and optoelectronic properties

Abstract: In this paper, we have synthesized four simple twisting arylvinyl anthracene derivatives, 9-styrylanthracene (ASB), 9,10-bis(styryl)anthracene (SB), 9-(2-(naphthalen-1-yl)vinyl)anthracene (ASN) and 9,10-bis((naphthalen-1-yl)vinyl)anthracene (SN), to demonstrate the effect of skeleton symmetry on optical and optoelectronic properties. The results showed that SB and SN are weak emission with the fluorescence quantum yields (Φ) of ca. 7 % but ASB and ASN are highly fluorescent (Φ ≈ 50 %) in THF solution, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Moreover, anthracene and its derivatives are widely used as the active layer in organic devices, and so their physicochemical properties and the spin dependent processes that occur within these devices are well documented. 19,[42][43][44][45][46][47][48] In this paper, we describe the investigation of the MC characteristics of T t PI and TP t I in anthracene-based OLEDs. The EL spectra, MEL curves and current-voltage characteristics indicated that the active anthracene layer contained large amounts of trapped singlet excitons (S 1t ), T t and P t .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anthracene and its derivatives are widely used as the active layer in organic devices, and so their physicochemical properties and the spin dependent processes that occur within these devices are well documented. 19,[42][43][44][45][46][47][48] In this paper, we describe the investigation of the MC characteristics of T t PI and TP t I in anthracene-based OLEDs. The EL spectra, MEL curves and current-voltage characteristics indicated that the active anthracene layer contained large amounts of trapped singlet excitons (S 1t ), T t and P t .…”
Section: Introductionmentioning
confidence: 99%
“…The conformationally controlled intramolecular torsional motions between the anthrylene center and vinylene fragments linked at 9, 10 positions play a great role in the observed AIEE phenomenon [2] . Also, the twisted molecular architecture originates from the strong repulsion between the 1, 4, 5, 8 positions in the anthracene moiety, and the aryl/vinyl substituent attached at 9, 10 positions facilitates the torsional motions in DSA derivatives [3] . A large number of AIEE active DSA derivatives were systematically investigated for the diverse applications till now.…”
Section: Introductionmentioning
confidence: 98%
“…[2] Also, the twisted molecular architecture originates from the strong repulsion between the 1, 4, 5, 8 positions in the anthracene moiety, and the aryl/vinyl substituent attached at 9, 10 positions facilitates the torsional motions in DSA derivatives. [3] A large number of AIEE active DSA derivatives were systematically investigated for the diverse applications till now. Recently multi aryl cyano substituted DSA derivatives were effectively utilized for the rewritable paper technology applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attaching Schiff base derivatives to organic or metal units to serve as optical sensors is a good approach for study . Only a few reports on anthracene derivatives are available, and these show high fluorescence efficiency in their solid states and the AIE/AIEE phenomenon . In addition, efforts have been made to design organic fluorophores coupled with the dynamic interactions of biologically important species that can be visualized by fluorescence microscopy .…”
Section: Introductionmentioning
confidence: 99%